Metaphorical conceptualization of success in American success books, aphorisms and quotes - Łącka-Badura, Jolanta (Lingua Posnaniensis, 2016)
The paper seeks to investigate how SUCCESS is conceptualized metaphorically in popular American success books, aphorisms and quotes. The study is based on an analysis of a corpus comprising over 600 utterances in which the lexical entry SUCCESS is regarded as constituting part of a metaphorical expression. The utterances have been extracted from the initial corpus of 10 success guide books, as well as 150 success aphorisms and quotes by famous Americans. The study investigates two aspects of this conceptualization. In the first instance, it examines which metaphorical source domains, as understood within the framework of Conceptual Metaphor Theory, prove to be most productive in the corpus. Secondly, in line with the frequently expressed views that the significance of conceptual metaphor as an explanatory construct is sometimes overstated in cognitive linguistic research, the paper attempts to analyze examples of linguistic metaphors which appear to be motivated in ways that are, at least in part, independent of well-established conceptual mappings, with particular emphasis on the resemblance-based and image metaphors associated with the predicate nominative forms ‘X is a Y’.